Assessing Nigeria’s progress toward monitoring and measuring of forest carbon in the context of REDD+ - Udeme Olayinka, Olaniyan; Paul, Dargusch; Ndifreke Edem, Ekom (Scientific Journal of Environmental Sciences, 2021)
Reducing emissions from deforestation and forest degradation in developing countries is considered an efficient and lowest-cost measure to mitigate climate change. Organizations like The United Nations Framework Convention on Climate Change (UNFCCC) and Intergovernmental Panel on Climate Change (IPCC), helps resolve essential challenges like availability/use of technology, administration, human capacity and low capacity to measure and quantify national forest carbon emission reductions from Reducing Emission from Deforestation and Forest Degradation (REDD+). This study assessed Nigeria’s progress in implementing the requirements for monitoring and quantifying forest carbon stock in the context of REDD+. This study was through a case study research where national and international REDD+ documents on MRV were reviewed and analyzed. The results showed that Nigeria had an average ranking score for the establishment of administrative/institutional capacity; however, they ranked low both in its ability to acquire and make available essential technical tools/methods; and in the adoption of REDD+ ethical governance principles. This study shows that the nation had made considerable efforts in establishing administrative/institutional capacity even though unable to acquire relevant technological methods/capacities, competence, expertise, and incorporate REDD+ good governance practice in MRV implementation. Findings of this study shows that high-order technical methods (e.g., remote-sensing and satellite land monitoring system-SLMS) are not freely available due to lack of financial capacity to acquire these tools. This study also reveals that there is low collaboration with communities and other key actors/stakeholders in the REDD+ MRV process. This study suggests that international organizations should lend support through the transfer and provision of technical tools/methods relevant for MRV, and this should be supplemented with training to develop vital capacity/skills for MRV. Also, Nigerian REDD+ administrative institution should encourage active inclusion and participation of all stakeholders, particularly, the local communities in its MRV implementation; their involvement will not only improve the monitoring and measurement of forest carbon stocks but will help in early identification of potential threats to the success and sustainability of the program.